Feudalist Symbols towards Behavior in the Novel The Girl Who Came Home by Hazel Gaynor - Nerry Anjelina; Rosmiati Rosmiati; Waladdin Panggabean (Faculty of Letters Universitas Balikpapan, 2019)
This thesis explores the feudalist symbols towards behavior in the novel The Girl Who Came Home by Hazel Gaynor. There are two objectives of this research; 1) to identify the forms of the feudalist symbols found in the novel The Girl Who Came Home by Hazel Gaynor and 2) to identify how the feudalist symbols influence the behavior found in the novel The Girl Who Came Home by Hazel Gaynor. The theory used in this research is the semiotic using Roland Barthes theory of feudalist symbols; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the words and sentences in the novel. The words and sentences in the novel were taken out as the primary data. The result of the research, the researcher finds that are eight forms of the feudalist symbols in The Girl Who Came Home by Hazel Gaynor, the forms are: 1) Want to always be respected 2) Limiting the association 3) The title of education 4) Dressing excessive 5) Showing off the wealth 6) The using of language 7) Limiting the unnecessary time 8) Disrespecting others. The researcher also finds the feudalist symbols influence the behavior, those are; Desperate, Arrogant and Selfish.